Service Quality and Organizational Culture on Taxpayer Compliance - Jumawan, Jumawan; Supardi, Supardi; Yulianah, Yulianah; Achmad, Willya (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research analyzes the influence of service quality and organizational culture on taxpayer compliance. The research approach used is quantitative research using survey methods. The data collection technique used in this research was a Likert scale questionnaire. The research sample comprised 100 taxpayer respondents at the Sumedang Regency Primary Tax Service Office. The research results show that service quality and organizational culture partially and simultaneously influence taxpayer compliance. This research contributes to understanding the factors influencing taxpayer compliance, especially regarding service quality and organizational culture. The results of this research can be used as a basis for increasing taxpayer compliance through improving service quality and developing a conducive organizational culture.